2008
DOI: 10.1017/s1751731108002309
|View full text |Cite
|
Sign up to set email alerts
|

Response of piglets weaned from sows fed diets supplemented with conjugated linoleic acid (CLA) to an Escherichia coli K88+ oral challenge

Abstract: Seventy-eight Cotswold piglets weaned from sows receiving 0% or 2% conjugated linoleic acid (CLA)-supplemented rations from day 85 of gestation through lactation were allocated to nursery diets (ND) according to their dam's lactation ration (LR) as follows (1) 0%-0% (0% CLA LR: 0% CLA ND, n 5 17); (2) 0%-2% (0% CLA LR: 2% CLA ND, n 5 17); (3) 2%-0% (2% CLA LR: 0% CLA ND, n 5 23); and (4) 2%-2% (2% CLA LR: 2% CLA ND, n 5 21). At 28 6 2 days of age all piglets received an oral Escherichia coli K88 1 (enterotoxig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
2
16
1
Order By: Relevance
“…The same conclusion is confirmed by Patterson et al. () who found significantly lower weight at weaning in piglets from sows fed with 2% of CLA before weaning against the control group (p < 0.05), despite balanced birth weight.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The same conclusion is confirmed by Patterson et al. () who found significantly lower weight at weaning in piglets from sows fed with 2% of CLA before weaning against the control group (p < 0.05), despite balanced birth weight.…”
Section: Discussionsupporting
confidence: 72%
“…Patterson et al. () proved a decrease in occurrence of inflammation of the intestinal mucosa as compared with piglets from control group (p < 0.05). The authors state that supplementing feed ration for gravid and lactating sows with conjugated linoleic acid is a practical strategy for increasing the transfer of passive immunity, improvement of immune status and the state of intestinal mucosa in piglets.…”
Section: Discussionmentioning
confidence: 94%
“…Piezska et al (2007) wrote that it showed a positive eff ect on values of haemoglobin and hematocrit. Patterson et al (2008) observed a decrease in cases of enteritides in piglets. Our results indicated better values of the parameter "number of weaned piglets", viz.…”
Section: Resultsmentioning
confidence: 88%
“…For example, using lactic acid-producing bacteria as probiotics produced positive responses to growth performance indices and controlling PWD in some studies (Lessard and Brisson, 1987;Shu et al, 2001;Taras et al, 2006) but not in others (Walsh et al, 2007). Likewise, inclusion of yeast culture in weanling pig diets yielded positive responses to indictors of gut health and growth performance indices in some studies (Mathew et al, 1998;Bontempo et al, 2006;van der Peet-Schwering et al, 2007) but not in others (Kornegay et al, 1995;van Heugten et al, 2003). Inconsistency in the results has been attributed to differences in dosage and type of strain of probiotic, sanitary environment and diet type (Bontempo et al, 2006).…”
Section: Establishment Of the Git Microbial Communitymentioning
confidence: 99%